Graphene oxide and reduced graphene oxide hybrids with spin crossover iron(iii) complexes1. Issue 10 (29th October 2015) - Murashima, Yusuke; Karim, Mohammad Razaul; Saigo, Naoto; Takehira, Hiroshi; Ohtani, Ryo; Nakamura, Masaaki; Koinuma, Michio; Lindoy, Leonard F.; Kuroiwa, Keita; Hayami, Shinya
<x xml:space="preserve">Abstract</x> Graphene oxide and reduced graphene oxide hybrids with spin crossover complexes show the coexistence of electron conduction and unique magnetic behaviors.